Research on engineering parameter perception and innovation application based on Internet of things - Yanfen LI; Xuetian ZHU (物联网学报)
Antenna engineering parameters are the benchmark of the wireless network planning and optimization.It is of great significance for reducing the difficulty of the network operation and optimization by acquiring engineering parameters through the Internet of things.Starting from the importance of antenna parameters,the key technology of antenna parameters perception based on the Internet of things was introduced,and an innovative application of 5G massive MIMO intelligence was proposed.The basic process and method were clarified,which lays the foundation for advancing the antenna technology for Internet of things.